Recent developments in endovascular interventions to sustain vascular access patency in haemodialysis patients. Issue 12 (5th December 2018) - Kitrou, Panagiotis; Papasotiriou, Marios; Katsanos, Konstantinos; Karnabatidis, Dimitrios; Goumenos, Dimitrios S; Papachristou, Evangelos
Abstract: There is amassed evidence regarding the use of endovascular procedures for the treatment of vascular access stenosis and thrombosis. A review was conducted based on available randomized trials, cohort studies and retrospective analyses published after 2000 on endovascular treatment of dysfunctional and thrombosed vascular access, with an aim to illustrate the available device and procedural options. The use of paclitaxel-coated balloons, cutting balloons and covered stents is described in the field of vascular access stenosis. The broad spectrum of available devices and endovascular declotting procedures ranging from thrombolysis to thrombectomy is also discussed. Overall, in this review we demonstrate the increasing role of endovascular procedures in vascular access treatment and the improved patency outcomes provided by the implementation of novel endovascular devices. Moreover, the improvement of post-intervention primary patency rates after endovascular declotting procedures and the shift to more thrombectomy-dependent procedures over time is also highlighted. In conclusion, endovascular treatment of dialysis access stenosis and thrombosis has an established role, owing to the implementation of sophisticated devices, allowing, when needed, the simultaneous treatment of thrombosis and the underlying stenosis.